2005
DOI: 10.1016/j.jcrs.2005.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of corneal wound-healing response in photorefractive keratectomy and laser-assisted subepithelial keratectomy

Abstract: At higher attempted corrections, LASEK-treated eyes showed less keratocyte apoptosis, myofibroblast transformation, and up-regulation in the synthesis of chondroitin sulfate than PRK-treated eyes. These differences may account for better visual acuities and less stromal haze in higher attempted corrections in LASEK-treated eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 25 publications
0
29
0
3
Order By: Relevance
“…This evidence was further complemented by recent laboratory experiments using human and rabbit corneas, which showed a mitigated keratocyte response to LASEK compared with PRK. 37,38 These reasons constituted to the choice of LASEK procedure in our patients.…”
Section: Perioperative Data and Early Postoperative Recoverymentioning
confidence: 95%
“…This evidence was further complemented by recent laboratory experiments using human and rabbit corneas, which showed a mitigated keratocyte response to LASEK compared with PRK. 37,38 These reasons constituted to the choice of LASEK procedure in our patients.…”
Section: Perioperative Data and Early Postoperative Recoverymentioning
confidence: 95%
“…According to recent findings reported by Esquenazi et al [8] , eyes treated with laser-assisted subepithelial keratectomy showed less keratocyte apoptosis, myofibroblast transformation, and upregulation in the synthesis of chondroitin sulphate than PRK-treated eyes. These differences may account for better visual acuities and less stromal haze after laser-assisted subepithelial keratectomy [8] .…”
Section: Introductionmentioning
confidence: 80%
“…These differences may account for better visual acuities and less stromal haze after laser-assisted subepithelial keratectomy [8] .…”
Section: Introductionmentioning
confidence: 99%
“…According to a previous study done by Esquenazi et al [8], after excimer photoablation, the eyes treated with laser-assisted epithelial keratomileusis showed less keratocyte apoptosis, myofibroblast transformation and upregulation in the synthesis of chondroitin sulfate than those treated with PRK. These differences may account for better visual acuities and less stromal haze in higher attempted corrections in the eyes treated with laser-assisted epithelial keratomileusis.…”
Section: Introductionmentioning
confidence: 96%